A Cycle‐Etching Approach Toward the Fabrication of Superamphiphobic Stainless Steel Surfaces With Excellent Anticorrosion Properties1 . Issue 6 (16th March 2017) - Wen, Ni; Peng, Shan; Yang, Xiaojun; Long, Mengying; Deng, Wanshun; Chen, Gongyun; Chen, Jiaqi; Deng, Wenli
Abstract : In this paper, a facile approach is developed for preparing superamphiphobic surfaces with excellent anticorrosion properties on 304 stainless steel (SS) substrates. This proposed methodology involves fabrication of micro/nano‐scale binary structures on SS substrates by a cycle‐etching approach (cycles of hydrofluoric acid etching and ultrasonic cleaning), and final fluoroalkylsilane modification. Wettability measurements reveal that the fabricated SS surfaces become super‐repellent toward water and peanut oil. By varying the times of cycle‐etching, the authors compare the relationship between morphological change and wettability. The potentiodynamic polarization curves and electrochemical impedance spectroscopy suggest that the fabricated SS surfaces have superior corrosion resistance. Abstract : A cycle‐etching approach is developed to fabricate the superamphiphobic stainless steel surfaces. The resulted stainless steel surfaces hold micro/nano binary structure even after ultrasonic cleaning, which become super‐repellent toward water (72 mN m –1 ) and peanut oil (34 mN m –1 ), and show static water contact angles of 159° and peanut oil contact angles of 153°, respectively.